2013
DOI: 10.1111/jpi.12061
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reverses tunicamycin‐induced endoplasmic reticulum stress in human hepatocellular carcinoma cells and improves cytotoxic response to doxorubicin by increasing CHOP and decreasing Survivin

Abstract: Chemoresistance in hepatocellular carcinoma (HCC) is associated with multiple cellular responses to environmental stresses, such as nutrient deprivation and hypoxia. Nevertheless, whether ER stress resulting from nutrient deprivation and tumor hypoxia contributes to drug resistance remains unclear. Melatonin increased the efficacy of chemotherapeutic drugs in hepatocellular carcinoma in our previous studies. However, the effects of melatonin on endoplasmic reticulum (ER) stress-induced resistance to chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 35 publications
5
60
1
Order By: Relevance
“…Particularly the PERK-mediated signaling pathway seems to be influenced, e.g. the transcriptional downregulation or reduced activation of PERK, EIF2α, ATF4, CHOP and GADD34 was detected by different researchers (Fan et al, 2013;Ji et al, 2012;Tunon et al, 2013;Wang et al, 2011;Zaouali et al, 2013).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 96%
“…Particularly the PERK-mediated signaling pathway seems to be influenced, e.g. the transcriptional downregulation or reduced activation of PERK, EIF2α, ATF4, CHOP and GADD34 was detected by different researchers (Fan et al, 2013;Ji et al, 2012;Tunon et al, 2013;Wang et al, 2011;Zaouali et al, 2013).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 96%
“…It has been documented that melatonin modulates the signalling of neuronal cell death [47] and bladder cancer cells induced by ERS [48]. Melatonin significantly reverses tunicamycin-induced ERS in human hepatocellular carcinoma cells and improves cytotoxic responses to doxorubicin by increasing the expression of CHOP [49]. A couple of studies revealed that melatonin alleviates Cd-induced cellular stress and germ cell apoptosis in testes [50] and prevents bisphenol A-induced apoptosis by controlling BCL2 expression and ameliorating oxidative stress in the testes and sperm [51].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of cooperative apoptosis induction might be related to reduced Bcl-2 expression and improved Bax and caspase3 expression [176]. Previous studies have shown that melatonin elevated the effects of some chemotherapeutic drugs in HCC [177]. A study identified the roles of melatonin in ER stress-induced resistance to chemotherapeutic agents in HCC.…”
Section: Protective Effects Of Melatonin On Hepatocarcinomamentioning
confidence: 99%